Moderating effect of sleep quality in the relationship between coping and distress among medical students - Perveen, Shahida; Malik, Najma Iqbal; Rehman, Muhammad Ebad ur; Khan, Muhammad Younas; Rehan, Syeda Tayyaba; Asghar, Muhammad Sohaib; Pakpour, Amir H.; Griffiths, Mark; Ullah, Irfan; Atta, Mohsin (Frontiers in Psychiatry, 2024)
The present study examined the moderating effects of sleep quality in the relationship between coping and distress among medical college students. Present study was conducted to ensure the mental health of medical students and to dig out the reasons behind their disturbed health which can directly impact their performance at work. The study utilized a cross-sectional survey and was distributed to students at various medical institutions in the Punjab province of Pakistan from October 2019 to June 2020. The sample comprised 369 participants (120 males; 32.5%). The survey included the Pittsburgh Sleep Quality Index (PSQI), Kessler Scale of Psychological Distress (K10), Brief Cope Scale, and Wong and Law Emotional Intelligence Scale. The results showed there was a significant relationship between coping and distress. More specifically, adaptive coping and distress were negatively associated (r=-.24), and maladaptive coping and distress were positively associated (r=.46). Moreover, the present study found that poor sleep quality was a significant positive predictor of distress. Moderation analysis showed that sleep quality was a significant moderator in the relationship between adaptive coping and distress (ΔR 2 =.011, β=-.36, p<.01) as well as between maladaptive coping and distress (ΔR 2 =.021, β=-.17, p<.01). The study's findings clearly showed that sleep quality is a significant moderator in the relationship between coping (both adaptive and maladaptive) and distress among medical students.